2017
DOI: 10.12659/msm.904404
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-495 Inhibits New Bone Regeneration via Targeting High Mobility Group AT-Hook 2 (HMGA2)

Abstract: BackgroundMicroRNAs play critical roles in post-translational gene expression. In this study, we explored the role of miR-495 in new bone regeneration.Material/MethodsMurine calvarial osteoblasts were isolated and cultured. Microarray was performed to identify differential miRNAs in medicarpin-induced osteoblasts differentiation. Luciferase reporter assay was performed to identify the target gene of miRNA. Murine osteoblast cells were transfected with miC, miR-495, or anti-miR-495. CCK-8 and flow cytometry wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…The effect of miR-98-5p on the osteogenic differentiation of the mouse preosteoblast cell line, MC3T3-E1, was subsequently investigated in the current study. Consistent with previous studies (27,29), the results of the present study demonstrated that miR-98-5p significantly inhibited MC3T3-E1 cell osteogenic differentiation by repressing the expression of HMGA2. In addition, miR-98-5p upregulation significantly inhibited cell viability and induced apoptosis in MC3T3-E1 cells and these effects were eliminated by HMGA2 overexpression.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The effect of miR-98-5p on the osteogenic differentiation of the mouse preosteoblast cell line, MC3T3-E1, was subsequently investigated in the current study. Consistent with previous studies (27,29), the results of the present study demonstrated that miR-98-5p significantly inhibited MC3T3-E1 cell osteogenic differentiation by repressing the expression of HMGA2. In addition, miR-98-5p upregulation significantly inhibited cell viability and induced apoptosis in MC3T3-E1 cells and these effects were eliminated by HMGA2 overexpression.…”
Section: Discussionsupporting
confidence: 93%
“…Wei et al (28) demonstrated that miR let-7 promoted MSC osteogenesis in vitro and in vivo by inhibiting HMGA2 expression (28). It has also been demonstrated that miR-495 prevents new bone regeneration by targeting HMGA2 (29). However, the association between miR-98-5p and HMGA2 has not yet been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Formosa et al (2014) further found that miR-154, miR-376a, miR-376c, miR-381, and miR-495 controlled metastatic prostate regulate cancer cells proliferation, apoptosis, migration, and invasion [69]. Additional research has identi ed miR-495 as an inhibitor of bone regeneration, gastric cancer cell migration, and invasion, potentially owing to its ability to target high-mobility group AT-Hook 2 [70,71]. We identi ed oar-miR-150, oar-miR-30a-3p, oar-miR-543-3p, oar-miR-412-3p, and oar-miR-154a-3p as DEMs in the present study, suggesting that they may be important regulators of metabolic activity and tail fat deposition in sheep.…”
Section: Discussionmentioning
confidence: 99%
“…A report has showed that miR-495 overexpression promoted murine calvarial OB apoptosis and inhibited proliferation obviously via targeting the high-mobility group, AT-Hook 2 (HMGA2), in their study (Z. Tian, Zhou, Xu, & Bai, 2017 mRNA. Overexpression of miR-182 in OB lineage cells not only inhibited osteoblastic differentiation and proliferation, but also increased cell apoptosis, and FoxO1 was identified as the target of miR-182 (K. M. Kim et al, 2012).…”
Section: Role Of Mirnas In the Apoptosis Of Obsmentioning
confidence: 98%